Pengaruh Likuiditas, Solvabilitas, Dan Profitabilitas Terhadap Harga Saham Pada Perusahaan Industri Barang Konsumsi Sub-Sektor Makanan Dan Minuman Yang Terdaftar Di BEI Tahun 2015-2019 - Lamsihar Rajagukguk; Nathania Mauriska Walani; Megawati Silaban (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of this research is to find out how the influence of Liquidity, Solvency, and Profitability either partially or simultaneously on stock prices. Each data used is official data from the annual financial statements taken from financial statements listed on the IDX. In obtaining the sample using purposive sampling, 50 samples were obtained from 10 companies in the food and beverage sub-sector consumer goods industry listed on the Indonesia Stock Exchange in 2015-2019. In testing the data, there are two tests used in this observation, namely the classical assumption test and hypothesis testing which are normality, multicollinearity, autocorrelation, heteroscedasticity and for hypothesis testing, the R2 coefficient of the partial hypothesis and the simultaneous hypothesis are used. Value of adjusted R square 22, 7% is influenced by the variable Current Ratio, Debt to Equity Ratio, Return On Assets on stock prices, 77.3% is influenced by other variables. The conclusion in this study is that the Current Ratio variable, Debt to Equity Ratio, has no or no significant impact on stock prices and the Return On Assets variable has a significant impact on stock prices. So Current Ratio, Debt to Equity Ratio, Return On Assets have a significant and simultaneous effect on stock prices. Keywords: Stock price, Current Ratio, Debt to Equity Ratio, Return On Assets